Meningkatkan Kemampuan Literasi Numerasi Anak Sekolah Dasar serta Menanggulangi Bullying di SD Negeri 070688 - Sianipar, Suriani Juwita; Atik, Tuti; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This teaching campus activity is a form of implementation of the Independent Learning Teaching Campus (MBKM) program with USU partners. This program is based on the decline in student interest in learning, the level of student learning comprehension, and students' reading and mathematics skills. Another old problem, intense interaction, may also be the reason why bullying occurs in schools . Through Field Work Practice (PKL 1), I brought the topic of mini project to elementary school students, namely Improving Numeracy Literacy Skills of Elementary School Children and Overcoming Bullying. Which is where students' learning ability will be very influential from the state of the school environment. Bullying culture in the name of seniority still occurs among elementary school students, bullying is mostly repeated, some are even planned. Character education is a way or means to overcome these problems. This work program has been carried out using the group work method consisting of the stages of Assessment, Planing / Planning, Intervention, Evaluation, and finally Termination. The Teaching Campus focus also helps make learning methods fun, such as simple and fast kabataku operations (multiplication, division, addition, subtraction), use of interactive learning environments and identification of students' math learning abilities. The end result of this program can be seen through the reduction in the number of students who commit bullying acts at school and the increase in interest in learning, reading and numeracy students at school.